A multi-model approach to engaging stakeholder and modellers in complex environmental problems. Issue 48 (April 2015) - Fulton, Elizabeth A.; Boschetti, Fabio; Sporcic, Miriana; Jones, Tod; Little, L. Richard; Dambacher, Jeffrey M.; Gray, Randall; Scott, Roger; Gorton, Rebecca
Highlights: Models of different size, complexity and scope can better address the needs of environmental management. We used five different model types in an effort to inform policy-making in regional multiple use management. We describe the different roles the models cover and how they facilitate stakeholder engagement. We conclude by summarising the lessons we learnt. Abstract: Models are increasingly used to support decision-making in the management of natural resources. They can provide system understanding, learning, a platform for stakeholder engagement, projections of system behaviour and an environment for virtual testing of alternative management strategies. However, rarely is a single numerical model suitable for all these purposes. Our experience is that a suite of models of different size, complexity and scope can be more effective and can better address the needs of environmental management projects. Models of different complexity can address different needs, but can also be combined as a flexibly sculpted tool kit – as they require very different development effort they can be deployed at different stages during a project. Using rapidly deployed qualitative, or simple quantitative, models stakeholders can be exposed to models very early in the project, eliciting feedback on appropriate model content and familiarity with the modelling process without affecting the development of more complex, resource intensive, models aimed at answering core management questions. This early and continuous stakeholder exposure to models provides flexibility in addressing specific novel questions as they arise during project development, as well as an opportunity for developing skills and changing both modellers and stakeholders' attitudes, as is often needed when facing complex problems. Using an example where we used five different model types in an effort to inform policy-making around regional multiple use management in north-western Australia, we describe (i) how each model type can be used, (ii) the different roles the models cover, and (iii) how they fit into a full decision making process and stakeholder engagement. We conclude by summarising the lessons we learnt.